Manganese(II) Complexes of Pentadentate Macrocyclic Schiff-base Ligands Containing Pyridine - Keypour, Hassan; Azadbakht, Reza; Javad Sabounchi, Seied (Asian Journal of Chemistry, 2016)
Two new Schiff base macrocyclic complexes of [MnL1(H2O)2]Cl2·H2O (1) and [MnL2(H2O)2]Cl2·H2O (2) have been prepared via cyclocondensation of 2,6-diacetylpyridine and N,N'-bis(2-aminophenyl)-1,3-propandiamine and/or N,N'-bis(2-aminophenyl)-1,4-butandiamine respectively and have been characterized spectroscopically. The ligands are 16- and 17-membered pentaaza macrocycles.